2004
DOI: 10.1021/jm049568z
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram Facilitates Intracellular Cu Uptake and Induces Apoptosis in Human Melanoma Cells

Abstract: The alcohol-abuse deterrent disulfiram (DSF) is shown to have a highly selective toxicity against melanoma in culture, inducing a largely apoptotic response, with much lower toxicity against several other cell lines. Melanoma cell lines derived from different stages (radial, vertical, and metastatic phase) were all sensitive to DSF treatment in vitro; melanocytes were only slightly affected. A required role of extracellular Cu is demonstrated for DSF toxicity. Low concentrations of DSF alone decreased the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
232
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(252 citation statements)
references
References 29 publications
9
232
0
1
Order By: Relevance
“…Recently, several independent groups, including this study, have identified DSF through high-throughput screens as a potential therapeutic for the treatment of various cancers including glioblastoma (14)(15)(16)(17)(18)(19). As DSF has been used clinically for over 60 years to treat alcoholism, its pharmacokinetics has been extensively studied and shown to have an excellent safety record at FDArecommended doses (20,21).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, several independent groups, including this study, have identified DSF through high-throughput screens as a potential therapeutic for the treatment of various cancers including glioblastoma (14)(15)(16)(17)(18)(19). As DSF has been used clinically for over 60 years to treat alcoholism, its pharmacokinetics has been extensively studied and shown to have an excellent safety record at FDArecommended doses (20,21).…”
Section: Introductionmentioning
confidence: 98%
“…DSF is available, inexpensive, safe, and overall well-tolerated making it an attractive candidate for "repurposing" in the context of glioblastoma. Although the anticancer mechanisms of DSF are still not well-understood (22), published data indicate that the cytotoxicity of DSF is enhanced in the presence of copper (14,15,23). DSF chelates bivalent metals such as copper (Cu) and zinc (Zn) to form DSF metal complexes that inhibit proteasome activity and block the degradation of IkB and NFkB nuclear translocation (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…According to this hypothesis, pro-oxidant pharmacological agents that substantially increase cellular ROS would induce deviations from redox homeostasis that do not reduce viability of untransformed cells, but cannot be tolerated by malignant cells that are already under high constitutive oxidative stress [1,12]. Indeed, prooxidant redox agents including metal-based drugs such as dithiocarbamate chelates [13] and therapeutics in advanced clinical development such as texaphyrins [14] can achieve cancer cell-selective cytotoxicity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer effect of DSF has been shown to be Cu dependent [37][38] However, the level of protection does depend on the formulation and sonication time used. The choice of PLGA has no significant (p > 0.05) influence on the level of DSF protection that the nanoparticles provide ( Figure 4A), which is due to the size of the nanoparticles being similar (Figure 2A).…”
Section: The Ability Of the 10% W/w Dsf-loaded Plga Nanoparticles To mentioning
confidence: 99%
“…This anticancer effect is copper (Cu) dependent [37][38] as Cu plays a crucial role in redox reactions which trigger the generation of reactive oxygen species (ROS) inducing apoptosis in human cells [39]. A recent phase IIb study demonstrated that DSF in combination with cisplatin and vinorelbine was well tolerated and prolonged the survival of patients with newly diagnosed NSCLC [40].…”
Section: Introductionmentioning
confidence: 99%